Trends in Clinical Deep Brain Stimulation - Janssen, Marcus L. F.; Temel, Yasin (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers the current trends in clinical deep brain stimulation (DBS) research. This collection of papers from experts in the field provides state of the art knowledge and future perspectives in clinical DBS research. A range of topics involved in DBS is presented, ranging from high resolution imaging, electrophysiology and personalized medicine, in a broad range of brain disorders.